PF Peningkatan Produktivitas dan Nilai Tambah Madu Kelulut melalui Inovasi Semen-Fero dan Pelatihan Pembuatan Sabun Madu di Kampung Temenin Lama–Malaysia - Yulcherlina Yulcherlina; Nor Hasanah binti Abdul Shukor Lim; Popi Fauziati; Khadavi Khadavi; Rizky Ananda Zulkarnain; Mentari Salmita (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2026)
Background: Stingless bee (kelulut) honey has significant economic potential for rural communities due to its rich bioactive composition and growing market demand. However, kelulut farmers in Kampung Temenin Lama still face limitations in product diversification, resulting in suboptimal income. This Community Service Program (PkM) aims to enhance the added value of kelulut honey through training in honey-based soap production and to improve honey productivity using innovative ferro-cement hive technology. Methods: The program was implemented in three stages: (1) preparation through field surveys, needs assessment, and training module development; (2) implementation through hands-on training on Melt & Pour soap-making techniques for 26 kelulut farmers; and (3) evaluation through assessing soap quality and participants’ mastery of the production process. Results: This program indicate a 35% increase in honey production within one year following the adoption of ferro-cement hives, along with the successful transfer of skills enabling farmers to process honey into higher-value products. The resulting kelulut honey soap demonstrated good characteristics in terms of shape, color, aroma, and functional benefits such as moisturizing effects, reduced skin irritation, antibacterial activity, and suitability for sensitive skin. Conclusions: this PkM program effectively improved honey productivity and expanded business opportunities through product diversification, thereby contributing to increased income and enhanced economic resilience among kelulut farmers in Kampung Temenin Lama. The program demonstrates that technological innovation combined with value-added product development can serve as a sustainable strategy for strengthening local community livelihoods.